NEW TUNNEL BASED METHOD OF SENSITIVITY MATRIX CALCULATION FOR 3D CAPACITANCE TOMOGRAPHY IMAGE RECONSTRUCTION - Wajman, Radosław; Banasiak, Robert (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The sensitivity matrix is main part of the image reconstruction process for 3D ECT imaging and strictly decides about the its final quality. Common sensitivity determination methods mostly provide acceptable results and additionally allow to perform the recalculation of the sensitivities according to the changing permittivity distribution. In this paper authors introduce the crucial modification of the sensitivity determination process based on the electric field distribution analysis. The designed new tunnel based algorithm follows the surfaces constructed along the electric field lines. In the paper the results of the image reconstruction experiments will be shown and the better accuracy of the new method will be proved.